Building Agility and Adaptive Governance Through Digital Bureaucracy Ecosystem for Innovative Public Policy - Tresiana, Novita; Duadji, Noverman; Jayamuna, I Made (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2024)
This study discusses the weaknesses of bureaucracy in responding to strategic development issues, especially related to low transparency and public participation. Causal factors include limited public governance capacity, lack of policy actor qualifications, and suboptimal use of digital technology in decision-making. The bureaucracy's focus on internal, operational, and administrative aspects also worsens these conditions. This study introduces the agile and adaptive governance approach, which allows the bureaucracy to work more strategically, flexibly, quickly, and adaptively in the VUCA era (Volatility, Uncertainty, Complexity, Ambiguity). The digital bureaucracy ecosystem (EBD) model was developed to integrate stakeholders, systems, and supporting environments through the use of digital technology. Using a multi-criteria decision-making method with a participatory approach, this study found that the EBD model is able to increase public governance capacity, transparency, and public participation. Digital integration also encourages the creation of an innovative and responsive public policy formulation process. Recommendations include strengthening the capacity of bureaucratic human resources through adaptive training, accelerating digital transformation, and comprehensive supporting policies. This research contributes to the development of an agile and adaptive public governance model, supports bureaucratic competitiveness, and encourages green digital initiatives as a step towards better governance in the era of globalization.